Stress, Anxiety and Depression in First-year Medical Undergraduates and Coping Strategies Employed during COVID-19-induced Online Learning: A Cross-sectional Study from North India - Rashmi Malhotra; Manisha Naithani; Anita Verma; Yogesh Bahurupi; Kanchan Bisht; Brijendra Singh; Tanmay Joshi (Journal of Medical Evidence)
Background: The COVID-19 pandemic, due to its rising uncertainties, was expected to negatively impact the overall psychological functioning of students undergoing first year of medical professional education with changing teaching styles and environmental restraints. Objective: The objective was to assess the impact of this stressful period on the first-year Bachelor of Medicine and Bachelor of Surgery (MBBS) students at an Institute of National importance in North India, by measuring their various emotional states such as stress, anxiety, depression and coping strategies. Methods: This was a descriptive cross-sectional study undertaken in first-year MBBS students who were admitted in February 2021 due to delay in the admission process. Their physical classes were suspended due to the onset of second wave of COVID-19 and underwent a significant shift from conventional classes to a hybrid teaching module involving online classes, minimal face-to-face contact with teachers and almost no practical exposure which is in contrast to the conventional teaching practices. Data collection was done during and in the aftermath of second wave of COVID-19 using the Depression, Anxiety and Stress Scale (DASS-21) to assess emotional state and the Brief-Coping Orientation to Problems Experienced Inventory to measure the coping strategies employed. Results: One hundred and twenty-five students were approached and 80 consented to participate. The 80 students were analysed. Elevated depressive symptomatology scores were found in 46% of students, of which 14% had scores falling in severe category. More than 62% had elevated anxiety scores, of which 26% had severe range of scores, and 37% students had elevated stress scores, of which more than 10% had severe range of scores. Venting, humour and self-blame were found to be the predominant facets of coping styles employed and they had a significant statistical correlation with all three subscales of DASS-21. Conclusion: The study found a significant prevalence of depressive, anxiety and stress symptomatology. These findings emphasise the need for mental health interventions and support programmes for medical college MBBS students to help them cope with the psychological impact of academic and personal stressors.